2014
DOI: 10.1021/jo500675a
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Coupling of Halophenols and Phenol Boronic Acids: Systematic Investigation of Positional Isomer Effects and Conclusions for the Synthesis of Phytoalexins from Pyrinae

Abstract: The Suzuki-Miyaura couplings of o-, m-, and p-halophenols with o-, m-, and p-phenol boronic acids were investigated for all combinations under standardized conditions, using Pd/C as a heterogeneous catalyst and water as a solvent. In the case of iodophenols, conventional heating was used, while for bromophenols significantly better results could be obtained using microwave irradiation. This systematic study revealed that 2,4'-biphenol is particularly difficult to access, irrespective of the starting materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…[37] In the next step, the o,pЈ-biphenol moiety was constructed by a Suzuki-Miyaura coupling reaction. [38] Fluorides are believed to coordinate to the Pd, increase the nucleophilicity of the solvent, that is, water, through hydrogen bonding, and thereby facilitate the formation of the crucial Pd-hydroxy intermediates [40][41][42] without extensive deprotonation of the boronophenol. [39] We found that bases such as NaOH or K 2 CO 3 that are typically used in Suzuki-Miyaura reactions give very low yields when combined with p-boronophenols such as 7, and this might be attributed to the deprotonation of the phenol under these reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[37] In the next step, the o,pЈ-biphenol moiety was constructed by a Suzuki-Miyaura coupling reaction. [38] Fluorides are believed to coordinate to the Pd, increase the nucleophilicity of the solvent, that is, water, through hydrogen bonding, and thereby facilitate the formation of the crucial Pd-hydroxy intermediates [40][41][42] without extensive deprotonation of the boronophenol. [39] We found that bases such as NaOH or K 2 CO 3 that are typically used in Suzuki-Miyaura reactions give very low yields when combined with p-boronophenols such as 7, and this might be attributed to the deprotonation of the phenol under these reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show that both electron‐rich and electron‐deficient aryl halides ( 2 – 12 ) were tolerated to produce cross‐coupled products in moderate to good yield as assessed by product peak intensities (Figure A–D). Comparison of the anisole family of precursors ( 2 – 5 ) revealed that the meta ‐positioned methoxy group ( 4 , Figure C) provided more desired product than ortho ( 5 , Figure D) or para ( 2 & 3 , Figure 3 A&B) due to the reduced electron donating contribution from the meta placement of this substituent …”
Section: Resultsmentioning
confidence: 99%
“…A careful evaluation on how the substituent position in 9 influenced the reaction efficiency was also reported: the m-boronophenol was the most reactive substrate, followed by the p-isomer. The optimized MW accelerated cross-coupling conditions were applied to the synthesis of nine naturally occurring phytoalexins with biaryl structures (Scheme 4) [22]. The cross-coupling occurred also under conventional heating (2.5 h at 80 °C vs. 30 min at 150 °C under MW irradiation) while, with the corresponding bromophenols, the products were obtained in acceptable yields only using MWs.…”
Section: Suzuki-miyaura Couplingmentioning
confidence: 99%